Activation of p21(CIP1/WAF1) in mammary epithelium accelerates mammary tumorigenesis and promotes lung metastasis - Cheng, Xiaoyun; Xia, Weiya; Yang, Jer-Yen; Hsu, Jennifer L.; Chou, Chao-Kai; Sun, Hui-Lung; Wyszomierski, Shannon L.; Mills, Gordon B.; Muller, William J.; Yu, Dihua; Hung, Mien-Chie (Biochemical and biophysical research communications, 2010)
► Akt-activated p21 was primarily expressed in cytoplasm of cells in transgenic mice. ► Akt-activated p21 accelerated tumor onset in MMTV/neu mice. ► Akt-activated p21 promoted lung metastasis in MMTV/neu mice. ► In vivo evidence that cytoplasmic p21 functions as an oncogene. While p21 is well known to inhibit cyclin-CDK activity in the nucleus and it has also been demonstrated to have oncogenic properties in different types of human cancers. In vitro studies showed that the oncogenic function of p21is closely related to its cytoplasmic localization. However, it is unclear whether cytoplasmic p21 contributes to tumorigenesis in vivo. To address this question, we generated transgenic mice expressing the Akt-phosphorylated form of p21 (p21T145D) in the mammary epithelium. The results showed that Akt-activated p21 was expressed in the cytoplasm of mammary epithelium. Overexpression of Akt-activated p21 accelerated tumor onset and promoted lung metastasis in MMTV/neu mice, providing evidence that p21, especially cytoplasmic phosphorylated p21, has an oncogenic role in promoting mammary tumorigenesis and metastasis.